Submission and Settlement of Tax Disputes Through Objection, Appeal, and Judicial Review - Hafiz Indra Fata; Galuh Tresna Murti; Muhammad Dhani Raharja; Fathan Rifqi Al-Hakim; Muhammad Neza Qatrunada (Jurnal Riset Perpajakan: Amnesty, 2023)
The purpose of this study is to determine the likelihood that a conflicting party will prevail in a tax dispute case. The analysis of conflicting parties winning tax dispute cases promises to identify taxpayers. By using normative juridical research, this research uses the methodology of the law, this research is to examine Indonesia's efforts in filing and resolving tax disputes. The findings of this study found that to overcome the above problems, alternatives to filing and resolving tax disputes are needed, such as mediation of tax disputes by independent parties. Therefore, the researcher suggests that a tax dispute resolution and mediation institution, a non-ministerial government institution, should be established to handle objections and become an independent mediator of tax disputes between taxpayers and the Directorate General of Taxes.